Generalized morphea following COVID‐19 vaccine: Case report and literature review. Issue 4 (30th March 2023) - Alhayaza, Raid; Alhayaza, Ghada; Algarni, Abdullah; Alhumidi, Ahmed; AlHarithy, Ruaa
Abstract: Physicians should be vigilant for COVID‐19 vaccine side effects and investigate any associated cutaneous manifestations. This will ultimately facilitate better understanding and recognition of various skin reactions related to the vaccine.